1999
DOI: 10.1136/bjo.83.9.1032
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of dacryocystography and lacrimal scintigraphy in the diagnosis of functional nasolacrimal duct obstruction

Abstract: Aim-It appears from the literature that no standardised examination exists for patients with functional nasolacrimal duct obstruction. The role of dacryocystography and lacrimal scintigraphy was compared in the diagnosis and management of these patients. Method-Patients who were clinically diagnosed as having unilateral or bilateral functional nasolacrimal duct obstruction were prospectively entered into the study and data collected over 12 months in Moorfields Eye Hospital and Whipps Cross Hospital, London. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
71
2
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(81 citation statements)
references
References 9 publications
4
71
2
2
Order By: Relevance
“…The sensitivities of lacrimal scintigraphy for detecting obstruction in the symptomatic patients were reported 81.6% by Jabbour et al, 77% by Rose et al and 95% by Wearne et al The sensitivity of 96.3% and specificity of 90.4% were reported by Fard-Esfahani et al [14][15][16][17]. Our study showed high sensitivity (96.3%) and specificity (75.5%) as shown by previous studies mentioned above especially having the "after wash" studies.…”
Section: Discussionsupporting
confidence: 76%
“…The sensitivities of lacrimal scintigraphy for detecting obstruction in the symptomatic patients were reported 81.6% by Jabbour et al, 77% by Rose et al and 95% by Wearne et al The sensitivity of 96.3% and specificity of 90.4% were reported by Fard-Esfahani et al [14][15][16][17]. Our study showed high sensitivity (96.3%) and specificity (75.5%) as shown by previous studies mentioned above especially having the "after wash" studies.…”
Section: Discussionsupporting
confidence: 76%
“…O exame radiográfico contrastado realizado prestou-se como método de reconhecimento da anatomia e da localização das estruturas do sistema de drenagem lacrimal dos cães, proporcionando, também, a verificação da patência dessas estruturas, conforme também relatado por vários autores na Medicina e na Veterinária, como Caye et al (1986), Slatter (1990a), Habin (1993), Barnett et al (1995), Takano & Mendonça Júnior (1996), Carneiro Filho (1997, Pereira et al (1997), Shankar et al (1999), Stades et al (1999), Wearne et al (1999), Grahn (2002), Gelatt (2003, Winston & Prasse (2003), Kleiner et al (2004), Nykamp et al (2004) e Silva (2004), que apontam a dacriocistografia como importante exame auxiliar. No presente trabalho, foi possível avaliar anatomicamente o sistema lacrimonasal também pela dacriocistografia por tomografia computadorizada contrastada, o que auxiliou na avaliação do sistema lacrimonasal em pacientes com alterações nas vias lacrimais concordando com os autores Costa et al (1997) que afirmaram que a semiologia da via lacrimal excretora envolve dados da anamnese, avaliação anatômica e funcional.…”
Section: Discussionunclassified
“…The CT-or MRI-DCG can determine if an anatomic obstruction exists within the outflow system, where the obstruction occurs, and gives excellent anatomic details, being of great help . On the other hand, the DSG performed with technetium-99m pertechnetate or technetium-99m-labeled sulfur colloid has a low resolution and lack of anatomical details 8,9 . In our cases, we used the Jones test, probing and irrigation associated with a cranio-facial CT or MRI scan.…”
Section: Discussionmentioning
confidence: 99%